2019
DOI: 10.1128/jvi.02052-18
|View full text |Cite
|
Sign up to set email alerts
|

The Carboxyl Terminus of Tegument Protein pUL21 Contributes to Pseudorabies Virus Neuroinvasion

Abstract: Following its entry into cells, pseudorabies virus (PRV) utilizes microtubules to deliver its nucleocapsid to the nucleus. Previous studies have shown that PRV VP1/2 is an effector of dynein-mediated capsid transport. However, the mechanism of PRV for recruiting microtubule motor proteins for successful neuroinvasion and neurovirulence is not well understood. Here, we provide evidence that PRV pUL21 is an inner tegument protein. We tested its interaction with the cytoplasmic light chains using a bimolecular fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 77 publications
0
27
0
Order By: Relevance
“…pUL21 has been implicated in different steps of the viral replication cycle in non-neuronal and neuronal cells [39,[62][63][64][65][66][67]. In particular, mutations in or complete absence of pUL21 affect retrograde transport processes in neurons [68,69], and point mutations in the UL21 gene of live-attenuated vaccine strain PrV-Bartha contribute to its avirulence in pigs [42]. Repair of the UL21 locus in PrV-Bartha has been shown to enhance retrograde intraaxonal and transneuronal spread [69].…”
Section: Plos Pathogensmentioning
confidence: 99%
See 2 more Smart Citations
“…pUL21 has been implicated in different steps of the viral replication cycle in non-neuronal and neuronal cells [39,[62][63][64][65][66][67]. In particular, mutations in or complete absence of pUL21 affect retrograde transport processes in neurons [68,69], and point mutations in the UL21 gene of live-attenuated vaccine strain PrV-Bartha contribute to its avirulence in pigs [42]. Repair of the UL21 locus in PrV-Bartha has been shown to enhance retrograde intraaxonal and transneuronal spread [69].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Repair of the UL21 locus in PrV-Bartha has been shown to enhance retrograde intraaxonal and transneuronal spread [69]. The delay in retrograde transport of UL21-null PrV has been linked to an interaction of the carboxyl terminus of pUL21 with Roadblock-1, a dynein light chain belonging to the dynein motor complex important for retrograde transport along microtubules [68]. Mice infected intraocularly or intranasally with a UL21-deleted PrV showed prolonged survival times compared to mice infected with wildtype virus [68] confirming previous results that pUL21 has an impact on neuroinvasion and spread [28].…”
Section: Plos Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudorabies virus (PrV) pUL21 has been extensively studied as mutations in the gene encoding this protein contribute to the attenuation of the vaccine strain Bartha (Klupp et al, 1995). PrV pUL21 is required for neurovirulence and a recent study identified that pUL21 binds the dynein light chain protein Roadblock-1, promoting retrograde axonal transport (Yan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…UL21 is another protein associated with neuroinvasion. It can promote PRV retrograde transport through interaction with cytoplasmic dynein light chain Roadblock-1 (Yan et al, 2019); however, UL21 mutation causes a delay in the spread to presynaptic neurons and reduces infectious particle production (Curanovic et al, 2009).…”
Section: Introductionmentioning
confidence: 99%